2005
DOI: 10.1111/j.1460-9568.2005.04104.x
|View full text |Cite
|
Sign up to set email alerts
|

Orexin and MCH neurons express c‐Fos differently after sleep deprivation vs. recovery and bear different adrenergic receptors

Abstract: Though overlapping in distribution within the posterior hypothalamus, neurons containing orexin (Orx) and melanin concentrating hormone (MCH) may play different roles in the regulation of behavioural state. In the present study in rats, we tested whether they express c-Fos differently after total sleep deprivation (SD) vs. sleep recovery (SR). Whereas c-Fos expression was increased in Orx neurons after SD, it was increased in MCH neurons after SR. We reasoned that Orx and MCH neurons could be differently modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
147
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(160 citation statements)
references
References 63 publications
12
147
1
Order By: Relevance
“…This result also differs from the findings of Modirrousta et al; they described an increase in the number of Fos immunoreactive MCHergic neurons in a paradigm of sleep rebound (mainly QS) after sleep deprivation in rats compared to wakefulness (Modirrousta, et al, 2005). However, it is interesting to note that the number of Fos expressing MCHergic neurons during the sleep rebound was small (3% of the total number of MCHergic neurons).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result also differs from the findings of Modirrousta et al; they described an increase in the number of Fos immunoreactive MCHergic neurons in a paradigm of sleep rebound (mainly QS) after sleep deprivation in rats compared to wakefulness (Modirrousta, et al, 2005). However, it is interesting to note that the number of Fos expressing MCHergic neurons during the sleep rebound was small (3% of the total number of MCHergic neurons).…”
Section: Discussioncontrasting
confidence: 99%
“…MCH was stained brown while Fos, which was stained black, concentrated in the nucleus. In view of published reports of Fos labeling in MCH-containing cells of the rat during AS rebound (Verret, et al, 2003) or total sleep rebound paradigms (Modirrousta, et al, 2005), it was an unexpected finding that, in our preparation, MCHergic neurons did not exhibit Fos immunoreactivity throughout the hypothalamus in any of the conditions studied (Fig. 5).…”
Section: Fos Immunoreactivity Of Mch-containing Neuronssupporting
confidence: 50%
See 1 more Smart Citation
“…Consistent with these findings, we found that OLZ induced the activation of 38% of the orexin neurons of the LH/PFA in rat brain, whereas a negligible amount of Fos-LI was seen in MCH neurons. This suggests a heterogeneity between these two groups of orexigenic neurons in regard to their neural connectivity and roles in the regulation of behavioral state (Cvetkovic et al, 2004;Modirrousta et al, 2005). Although the exact mechanism of OLZ-associated weight gain is unknown, OLZ may be better characterized by the analysis of Fos-LI in nuclei receiving projections from orexin neurons with connections to feeding-circuit regions and reward pathways of the rat brain (Harris and AstonJones, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Later, a strong connection between MCH and REMS has been revealed (Kitka et al 2011;Torterolo et al 2011). Local or intracerebroventricular administration of MCH to rodents caused a marked increase in REMS; moreover, an elevated activation (increased Fos immunoreactivity) of MCH-expressing neurons has been reported during REMS rebound after a long-term sleep deprivation (Hanriot et al 2007;Kitka et al 2011;Modirrousta et al 2005;Peyron et al 2009;Torterolo et al 2011;Verret et al 2003). The increase in the time spent in REMS and the decrease in the REMS latency during the rebound following sleep deprivation are both changes similar to those described in depression.…”
Section: Introductionmentioning
confidence: 99%